Pembuatan Konsentrat Protein Ampas Tahu Menggunakan Garam Ammonium Sulfat: Manufacturing of Tofu Pulp Protein Concentrate Using Ammonium Sulphate - Nurhaeni; Frischa Sari Kencana; Andi Tenri Ajeng; Khairuddin; Prismawiryanti; Syamsuddin; Dwi Juli Puspitasari; Indriani; Erwin Abdul Rahim (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2022)
Tofu pulp which generally becomes waste can be used as a source of protein concentrate. Protein concentrates from tofu pulp have been obtained at various ratios of tofu pulp: ammonium sulfate and ammonium sulfate salt concentration. The research was conducted to obtain the highest protein yield and content of tofu pulp protein concentrate. This study used a completely randomized design (CRD) with the independent variable being the ratio of tofu pulp filtrate: ammonium sulfate (1:2, 1:3, 1:4, 1:5, 1:6, and 1:7 (v/v)) and concentrations of ammonium sulfate (30, 40, 50, 60, 70, and 80%), while the dependent variables were the yield of protein concentrate and protein content. Production of protein concentrate used the salting-out method with ammonium sulfate salt. The ratio of tofu pulp: ammonium sulfate 70% obtained the best ratio of 1:5 with a yield of 41.6% and protein content of 84.58%. Tofu pulp as industrial waste can be a potential source of protein concentrate because it has a high protein content.